40.0k views
1 vote
Simplify the expression insert

Simplify the expression insert-example-1

1 Answer

5 votes
First, we are going to perform the division of the fraction inside the radical:

(96)/(8) =12
So, we can rewrite our radical as follows:

\sqrt{ (96)/(8)} = √(12)

Now, we are going to decompose 12 into prime factors:

12=2^2*3
So, we can rewrite our fraction as follows:

√(12) = √(2^2*3)

Since 2 has the same exponent as the index of the radical, we can take it out:

√(2^2*3)=2 √(3)

We can conclude that the simplified form of the expression is:
2 √(3)
User Imbearr
by
5.6k points